2020
DOI: 10.1785/0120200185
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Investigations of the Instrument Response for Distributed Acoustic Sensing (DAS) across 17 Octaves

Abstract: With the potential of high temporal and spatial sampling and the capability of utilizing existing fiber-optic infrastructure, distributed acoustic sensing (DAS) is in the process of revolutionizing geophysical ground-motion measurements, especially in remote and urban areas, where conventional seismic networks may be difficult to deploy. Yet, for DAS to become an established method, we must ensure that accurate amplitude and phase information can be obtained. Furthermore, as DAS is spreading into many differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 18 publications
1
45
0
Order By: Relevance
“…In order to characterize the instrument response of fiber-optic cables used for distributed acoustic sensing, Wang et al [ 46 ] and Lindsey et al [ 47 ] co-located fiber-optic DAS-arrays with conventional seismometers and compared the direct strain measurement to the strain that was obtained by finite differencing of two seismometer waveforms. In these studies, the observations match well for signal periods from 10 s to 120 s. Paitz et al [ 48 ] extended the frequency range for this kind of comparison and found a good match of observations for frequencies from 1/3000 Hz to 60 Hz.…”
Section: Introductionmentioning
confidence: 56%
“…In order to characterize the instrument response of fiber-optic cables used for distributed acoustic sensing, Wang et al [ 46 ] and Lindsey et al [ 47 ] co-located fiber-optic DAS-arrays with conventional seismometers and compared the direct strain measurement to the strain that was obtained by finite differencing of two seismometer waveforms. In these studies, the observations match well for signal periods from 10 s to 120 s. Paitz et al [ 48 ] extended the frequency range for this kind of comparison and found a good match of observations for frequencies from 1/3000 Hz to 60 Hz.…”
Section: Introductionmentioning
confidence: 56%
“…The recorded DAS noise arises from several natural sources, including ocean‐solid earth interactions, which produce surface gravity waves and microseisms, which are recorded at frequencies where DAS response is flat (e.g., Lindsey et al., 2020; Paitz et al., 2020). The natural noise amplitude can be affected by local seismic amplification effects.…”
Section: Das Noise Analysismentioning
confidence: 99%
“…To further investigate the response of underwater DAS to transient ground deformations, DAS signals are compared to the ground motion measurements recorded by nearby seismometers. The ability to convert DAS records to ground motions was investigated and demonstrated by several previous studies (e.g., Daley et al., 2016; Lindsey et al., 2020; Paitz et al., 2020; Wang et al., 2018). To convert strain‐rate records to ground motions, phase velocities need to be determined.…”
Section: Das Earthquake Signalsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the instrument response of DAS is broader than that of traditional receivers. However, it requires careful treatment and calibration as the fiber properties, casing, and installation method can influence it [31,[48][49][50]. A virtual DAS receiver is a single-axis measurement sensor, which is sensiti strain (or strain-rate) along the direction of the fiber.…”
Section: Introductionmentioning
confidence: 99%